Use of the PREPARE (PREhabilitation, Physical Activity and exeRcisE) program to improve outcomes after lumbar fusion surgery for severe low back pain: a study protocol of a person-centred randomised controlled trial. Issue 1 (December 2016) - Lotzke, Hanna; Jakobsson, Max; Brisby, Helena; Gutke, Annelie; Hägg, Olle; Smeets, Rob; den Hollander, Marlies; Olsson, Lars-Eric; Lundberg, Mari
Abstract Background Following lumbar fusion surgery, a successful outcome is empirically linked to effective rehabilitation. While rehabilitation is typically postoperative, the phase before surgery – termedprehabilitation – is reportedly an ideal time to prepare the patient. There are presently no guidelines for prehabilitation before lumbar fusion surgery. Physical activity has well-known health benefits, and staying physically active despite pain is a major principle in non-pharmacological chronic low back pain treatment. Psychological factors such as fear of movement, pain catastrophizing and low self-efficacy are known to be barriers to staying active. No studies have investigated prehabilitation protocols that promote physical activity and target psychological risk factors before lumbar fusion surgery. The aim of our proposed randomised controlled trial is to investigate whether patients who undergo lumbar fusion surgery for degenerative disc disease experience better functioning with a physiotherapeutic prehabilitation program (PREPARE) based on a cognitive behavioural approach compared to conventional care. Methods/Design We will recruit 110 patients between 18–70 years of age with degenerative disc disease who are waiting for lumbar fusion surgery. These patients will be randomly assigned to receive either PREPARE or conventional care. PREPARE uses a person-centred perspective and focuses on promoting physical activity and targeting psychological risk factors before surgery. The primary outcome will be disability measured using the Oswestry Disability Index 2.0. Secondary outcomes will include functioning (patient-reported and performance-based), physical activity (accelerometer), health-related quality of life, back and leg pain intensity, pain catastrophizing, kinesiophobia, self-efficacy, depression, anxiety, satisfaction with treatment results and health economic factors. Data will be collected at baseline (preoperatively) after the intervention (preoperatively), 3 and 8 weeks, 3, 6, 12, 24 and 60 months postoperatively. Discussion We hypothesise that the focus on promoting physical activity and targeting psychological risk factors before surgery will decrease disability and help the patients to be more active despite pain both before and after surgery. We will use a combination of outcome measures both patient-reported and performance-based, as well as accelerometer data. This will provide a more comprehensive picture of the patient's functioning than just patient-reported outcomes alone. Trial registration Current Controlled TrialsISCRTN17115599, Retrospectively Registered 18 May 2015.